Religion and the Good Life - Sarot, Marcel; Stoker, W. (Brill Book Archive Part 1, ISBN: 9789004472495., 2004)
Studies in Theology and Religion,10 In this volume, fourteen philosophers of religion reflect on religious views of the good life. Some authors focus on positive religion and its specific religious representations of the good life, while others abstract from these and focus on philosophical religion and its conceptual articulations of the good life. The tension between positive religion and philosophical religion, between representation and concept, is itself also analyzed. This volume is a result of the co-operation of the philosophers of religion who are senior members of the Netherlands School for Advanced Studies in Theology and Religion NOSTER. Religion and the Good Life Religion and the Good Life: Introduction - Marcel Sarot (Utrecht) and Wessel Stoker (Amsterdam) PART I - THE RELATIONSHIP BETWEEN REPRESENTATION AND CONCEPT The Tension between Representation and Concept as a Challenge for Philosophy of Religion - Peter Jonkers (Utrecht) Beyond Representation and Concept: The Language of Testimony - R.D.N. van Riessen (Kampen) PART II - THE TENSION BETWEEN REPRESENTATION AND CONCEPT Seduction and Guidance: Some Remarks on the Ambiguities of Reason and Reflective Thought in Connection with Religion and the Good Life - W. Dupré (Nijmegen) The Good Life is Historical - Ben Vedder (Nijmegen) The Quality of Life: Comic Vision in Charles Dickens and Iris Murdoch - Henry Jansen (Amsterdam) Narrative, Atonement, and the Christian Conception of the Good Life - Gijsbert van den Brink (Leyden) Myths and the Good Life: Ricoeur's Hermeneutical Approach to Myth - Wessel Stoker (Amsterdam) Bhajans and their Symbols: Religious Hermeneutics of "the Good Life" - Hendrik M. Vroom (Amsterdam) PART III - REPRESENTATIONS OF THE GOOD LIFE Models of the Good Life - Marcel Sarot (Utrecht) The Highest Good and the Kingdom of God in the Philosophy of Kant: A Moral Concept and a Religious Metaphor of the Good Life - Donald Loose (Tilburg-Rotterdam) Jacques Derrida and Messianity - Victor Kal (Amsterdam) Skepticism and the Meaning of Life - Michael Scott (Manchester) Ultimate Happiness and the Love of God - Vincent Brümmer (Utrecht) Human Being and the Natural Desire for God: Reflections on the Natural and the Supernatural - Eef Dekker (Utrecht).